Retinoblastoma - Rodriguez-Galindo, Carlos; Wilson, Matthew W.; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2010)
Treatment of retinoblastoma has evolved at a significant speed over the last two decades; ocular salvage approaches are now at the core of modern treatments, and assessment of visual and functional outcomes has become a priority. New discoveries in retinoblastoma biology are leading the way to the development of targeted therapies that could revolutionize our current approaches to the treatment. In this book, experts address all the important aspects of research and therapy - from biology to epidemiology to treatment. Retinoblastoma will provide a single source for the diagnosis and care of children with this malignancy.
Biology of Retinoblastoma -- Epidemiology -- Clinical Features, Diagnosis, Pathology -- Genetics of Retinoblastoma and Genetic Counseling -- Radiation Therapy in the Management of Retinoblastoma -- Chemotherapy in the Management of Retinoblastoma -- Treatment of Intraocular Retinoblastoma -- Treatment of Extraocular and Metastatic Retinoblastoma -- Second Malignancies and Other Long Term Effects in Retinoblastoma Survivors -- Visual Rehabilitation -- Retinoblastoma in Developing Countries.
Keywords: MEDICINE; RADIOLOGY, MEDICAL; ONCOLOGY; OPHTHALMOLOGY; PEDIATRICS; SURGERY; MEDICINE & PUBLIC HEALTH; ONCOLOGY; OPHTHALMOLOGY; PEDIATRICS; IMAGING / RADIOLOGY; PEDIATRIC SURGERY